Seeking the future journalist: An industry perspective on skills and roles - Spyridou, Lia Paschalia; Demetriou-Drousioti, Sophie (My University, 2022)
Journalism education has been the subject of debate and contention for more than 100 years. Drastic technological developments, the disruption of journalism’s traditional business model, and more recently the Covid-19 pandemic have inevitably sparked a new debate on the content and purpose of tertiary journalism education (Mensing, 2010; Marinho & Sánchez-García, 2022). The most prevalent and persistent aspect of journalism education has been the theory-practice division, which basically reflects the opposing views between academia and the industry (Josephi, 2016). Employers and editors see university-based journalism programmes as theory-laden and out of touch with industry realities (Robinson, 2016), whilst academics insist on the study of journalism in terms of its role, history, law, ethics, standards, methods and impact along with practice (Jarvis, 2012). Although the debate never really ended, since the early 2000s the idea of educating future journalists as ‘reflective practitioners’ seemed to have taken hold (Josephi, 2016). The advent of computational journalism (Thurman, 2017) on the one hand, and serious challenges ranging from shrinking budgets, severe criticisms of outdated curricula and students being skeptical whether the degree will land them a paying job (Robinson, 2016), resulted in journalism schools opting to become more industry and technology-oriented (Schmidt 2018). Curricula experiements have offered mixed findings; the addition of technology courses and social media elective modules have been hasty with questionable results, whilst internships, although in some cases proved helpful for preparing young professionals for a career in journalism, in other cases brought up instances of labor exploitation and minimal professional benefits (Senat et al, 2019). Some argue that such moves simply reinforce the alignment of journalism education with an industry-conceived model of journalism (Mensing, 2010); a model which emphasises the tenets of the ‘super journalist paradigm’ at the detriment of relevant, explanatory, well-sourced and well-verified journalism (Spyridou & Veglis, 2016). Meier & Schützender (2019) argue that one of the core qualifications that future journalists should have is to communicate constructive solutions; their suggestion draws on the science-practice combination “to go beyond the current professional model”. The issues of media literacy and critical thinking are being raised by Friesem (2019) as important skills to help future journalists not only comprehend economics, ideology, and power relations but also as important means to deconstruct information disorder in the post-truth era. The current professional and material conditions of journalism designate that the debate needs to go beyond the theory-practice division; rather it is necessary to re-examine the “core journalistic competencies as a response” to the ever-changing landscape (Guo & Volz, 2021, p. 93). Drawing on the notions of skills and professional roles, this study investigates how the industry envisions the future journalist; what type of skills do media organizations expect from future journalists. What is the perceived role of journalism from an industry perspective? The study is based on twelve semi-structured interviews of senior editors working in the big media groups in Cyprus. The findings aim to contribute in the broader discussion of reforming journalism education
Keywords: Journalism education